Trauma en el deporte: una mirada preventiva (2000)
ABSTRACT: sports are considered to be a protective factor for human health. Its beneficial effects are varied and numerous in regard to the optimal functioning of the body. Nevertheless, some danarge can occur during physical performance. fortunately, the risk factors that determine sports injusries are well known and subsequently we can approach prevention so that the multitude of benefits may be obtained without the disturbance of any unfore see on injuries.